2015
DOI: 10.1002/ldr.2339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Land use and Land Cover Changes in the Coastal Area of Bangladesh using Landsat Imagery

Abstract: Coastal land use across the globe has experienced remarkable rapid change over the recent decades because of extraordinary anthropogenic pressure and climate variability and change. Therefore, quantitative information about coastal land use change is imperative for effective management and planning resources for sustainable development. We analysed the quantitative land use and land cover changes during 1989-2000-2010 periods in three important agroecological zones of the most vulnerable coastal region of Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…According to the national MFZ for 2011-2020, a total area of 2,496 km 2 of land will be reclaimed from 2011 to 2020 in CYS (Wang et al, 2014), which is only one half of our estimates based on the digitized data. Moreover, compared with other land use types, such as aquaculture and port, the industrialization and urbanization areas only account for a small proportion (10%) of the reclaimed land (Islam, Miah, & Inoue, 2016), which means that the scale and extent of coastal wetland reclamation in the next few years may far exceed our estimates. Meng et al (2017) suggested that neither economics nor population density but policies are the direct driving forces of China's reclamation of wetlands.…”
Section: The Influence Of Reclamation and Natural Changes In Mudflatsmentioning
confidence: 70%
“…According to the national MFZ for 2011-2020, a total area of 2,496 km 2 of land will be reclaimed from 2011 to 2020 in CYS (Wang et al, 2014), which is only one half of our estimates based on the digitized data. Moreover, compared with other land use types, such as aquaculture and port, the industrialization and urbanization areas only account for a small proportion (10%) of the reclaimed land (Islam, Miah, & Inoue, 2016), which means that the scale and extent of coastal wetland reclamation in the next few years may far exceed our estimates. Meng et al (2017) suggested that neither economics nor population density but policies are the direct driving forces of China's reclamation of wetlands.…”
Section: The Influence Of Reclamation and Natural Changes In Mudflatsmentioning
confidence: 70%
“…Hence, as a result of rapid economic activity along with high population pressure and environmental degradation, LULC in Bangladesh has changed very rapidly [15,16]. Empirical investigations [8,14,15,[19][20][21][22][23] have shown that along with factors like rapid population growth and economic development, land degradation, and sea-level rise are some of the other driving forces in the coastal region of Bangladesh that have led to rapid LULC transformations over different periods, and that these have been arguably more widespread and intense than in any other areas of the globe, and that these conditions continue to worsen, leading to ongoing degradation and damages in the ecological value of these vulnerable environments [8,20,23].…”
Section: Introductionmentioning
confidence: 99%
“…The use of remote sensing is today a key strategy to research the soil and the soil processes (Aucelli et al, 2016;Holleran et al, 2015;Kaiser et al, 2015;Van Eck et al, 2016). Throughout remote sensing we can observe the "behaviour" of the environment we live in -changes of soil, vegetation, landforms, land uses, and land management; what is the cause for these changes; and mainly what effects these changes have on the environment (De Mûelenaere et al, 2011;Gong et al, 2015;Islam et al, 2015;Zucca et al, 2014). All these changeswhether natural or anthropogenic -can be effectively and easily monitored with the use of small unmanned aircraft systems (sUAS).…”
Section: Introductionmentioning
confidence: 99%